DIGITAL BANK LEGAL CHALLENGES: SECURITY PROTECTION AND LEAKAGE OF CUSTOMER PERSONAL DATA - Sasea, Enny Martha; Sakmaf, Marius Suprianto (Awang Long Law Review, 2023)
Technology and digitalization are growing and affecting various economic and industrial fields, one of which is banking industry. The presence of technology and the phenomenon of digitalization has directed this industry to a digital transformation process through digital banking. Digital banking was developed to serve customers faster, easier, and in accordance with customer experience, itcan be done completely independently by customers while still paying attention to security aspects through optimizing digital technology systems. The presence of lifestyle integration, automation in banking services is an important aspect that needs attention. Security and customer trust are important for banks, socustomers trust banks as a one-stop service for their financial needs. However, the problem faced in the digital banking era is how fardigital banking can be done by improving the quality of service to customers while paying attention and without compromising transaction security. In addition, there are cyber security issues related to consumer data protection, which until now do not have special regulations to provide legal certainty. The urgency of consumer protection for digital banking services will be assessed using legal research methods with a doctrinal approach contained in primary and secondary legal materials. The purpose of this study is to examine and analyze the developments and legal challenges of digital banking consumer protection in Indonesia. Basically digital banking in Indonesia has regulations but only limited to two things, namely digital banking services and regulations regarding the legal status of the existence of digital banks in Indonesia. For digital banking services, it is regulated in POJK No.12/ POJK.03/2018. Meanwhile, the legal status of the existence of digital banks in Indonesia is regulated in POJK No.12/POJK.03/2021. The challenge of implementing digital banking includes 6 (six) aspects, one of which is customer protection of personal data and the risk of data leakage that does not yet have specific regulations governing it. The principle of effective customer protection in banking law is for common goals and can be implemented, so that each banks can serve and protect customers better without harming other parties.